Infrastructure and economic development in Sub-Saharan Africa - Calderán, César (Policy research working paper, 2008)
"An adequate supply of infrastructure services has long been viewed by both academics and policy makers as a key ingredient for economic development. Sub-Saharan Africa ranks consistently at the bottom of all developing regions in terms of infrastructure performance, and an increasing number of observers point to deficient infrastructure as a major obstacle for growth and poverty reduction across the region. This paper offers an empirical assessment of the impact of infrastructure development on growth and inequality, with a focus on Sub-Saharan Africa. The paper uses a comparative cross-regional perspective to place Africa's experience in the international context. Drawing from an updated data set of infrastructure quantity and quality indicators covering more than 100 countries and spanning the years 1960-2005, the paper estimates empirical growth and inequality equations including a standard set of control variables augmented by infrastructure quantity and quality measures, and controlling for the potential endogeneity of the latter. The estimates illustrate the potential contribution of infrastructure development to growth and equity across Africa. "--World Bank web site